Aerobic fitness, running performance and body composition of Czech elite male summer biathletes - Psotta, R.; Sverakova, D.; Bunc, V.; Seflova, I.; Hraský, P.; Martin, A. J. (International Journal of Fitness, 2009)
In contrast to distance track running, information on the physiological characteristics of athletes trained in cross-country running (summer) biathlon does not exist. Therefore the aim of the study was to assess the physiological profile of Czech elite male summer biathletes. Male summer biathletes (n=14) aged 22.9(±5.8) years, trained for 6-15 years, were tested using an incremental running test on the treadmill with a 5 % inclination. During the test selected cardiorespiratory and performance variables were assessed. Body fat, body cell mass (BCM) and extracellular mass (ECM) were assessed using the bio-electrical impedance method. Mean VO2max and peak running speed (vmax) were 64.3(±5.2) ml. kg-1 min-1 and 17.4(±1.2) km.h-1, respectively. The selected physiological and performance variables at the ventilatory threshold (VT) were as follows: VO2 = 53.0 (±5.0) ml. kg-1 min-1, % VO2max at the VT level = 82.6(±2.2%), speed of running = 14.4(±1.0) km.h-1, % vmax = 81.5(±7.1) % and the energy cost of running C = 3.78(±0.48) J.kg-1.m-1. Both maximal aerobic power and aerobic capacity of the biathletes was 5-10 % lower than those of middle and long distance track runners found in previous studies. The C in biathletes suggested that training with the majority of running on a course with variable slope and a natural surface could affect to a similar degree of mechanical adaptation as training with the majority of running on a flat track. The ECM/BCM ratio= 0.73(±0.08) found in summer biathletes suggested that summer biathlon training can affect changes in body composition which are similar to the adaptation to endurance high intensity exercise found in distance track runners. The data presented in this study can also serve as preliminary physiological standards for the evaluation of the training status in subjects involved in summer biathlon training.